Efektivitas Daun Sirsak (Annona muricata Linn) terhadap Penurunan Tekanan Darah Pada Hipertensi - Niputu Swastini (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Hypertension is a non-communicable disease that is often referred to as the "silent killer" which can be defined as a condition in which the blood vessels have high blood pressure (systolic blood pressure > 140 Soursop leaves are often used as an alternative treatment). hypertension. The content of soursop leaf which is estimated to reduce blood pressure is potassium ion. Result: to determine the effectiveness of soursop leaf (Annona muricata Linn) in reducing blood pressure in hypertension. Methods: Using literature studies from both national and international journals by summarizing the discussion topics and comparing The results are presented in each article. Results: Potassium ion has several mechanisms in lowering blood pressure, namely weakening myocardial contraction, increasing sodium excretion from the body, inhibiting renin release, causing vasodilation, and inhibiting endogenous vasoconstriction. High levels can increase sodium excretion, so that it can reduce blood volume and blood pressure. Flavonoids work as ACE inhibitors which will inhibit the change of AI into AII thereby reducing the secretion of antidiuretic hormone (ADH) which makes the amount of urine secretion increase and a lot of salt (NaCl) is released which eventually results in a decrease in blood pressure. Vitamin C also plays a role in lowering blood pressure, because it can modulate the production of nitric oxide. Conclusion: giving soursop leaves can reduce blood pressure levels in hypertension